Prognostic and predictive value of epigenetic biomarkers and clinical factors in upper tract urothelial carcinoma. (August 2015) - Xiong, Gengyan; Liu, Jin; Tang, Qi; Fan, Yu; Fang, Dong; Yang, Kaiwei; Xie, Feng; Zhang, Min; Zhang, Lei; Liu, Libo; Zhang, Cuijian; Yao, Lin; et al.
Aim: We conducted this study to identify gene promoter methylation status and clinical predictors for upper tract urothelial carcinoma (UTUC) patients.Materials & methods: Using methylation-sensitive PCR, we examined ten genes promoter methylation status in 687 UTUC patients.Results: A methylated promoter of three genes to predict higher tumor stage (T3 and T4), five genes to predict higher tumor grade (G3) and one gene to predict pN+ were certified in this study. Nine factors were significantly associated with poor cancer-specific survival. Six factors were considered as predictors to develop bladder recurrence after surgery.Conclusion: Methylation occurs commonly in UTUCs, may affect carcinogenic mechanisms, and is a well predictive factor for cancer-specific survival and bladder recurrence in UTUCs.